Effects of communication skills educational intervention of Mothers of - Mohamadi, Ashraf; Hajiamini, Zahra; Ebadi, Abbas; Fathi-Ashtiani, Ali; Aliasgari, Matin (Advances in Nursing & Midwifery, 2015)
Anxiety disorders are one of the most common mental disorders in children. In regard with the importance effect of appropriate communication among parents specially mothers and children, on mental health of children, this study investigated the effects of communication skills training for mothers on anxiety levels of school students in Tehran. Methods and Material: In a quasi-experimental study, 114 students in first grade class, in an area in Tehran and their mothers were included. Before the intervention , children’s anxiety was assessed by using the School Anxiety Scale –Teacher report (SAS-TR (SAS-TR), and mothers’ communication skills was measured by Queendom communication skills questionnaire. The mothers of the children in intervention group were provided a communication skills education program. Mothers of the children in control group were also provided with communication skills education after completion of the study. Two month after the educational intervention mothers’ communicational skills and their children’s anxiety in two groups were assessed by two questionnaires and compared with pre intervention stage. Data were analyzed by SPSS statistical software. Findings: Wilcoxon statistical test showed a significant decrease in anxiety scores of children of mothers of intervention group (p<0.05), while no significant difference was found between pre and post educational intervention anxiety scores in control group. Mean scores of mothers’ communicational skills was (114.± 8/9) before Intervention which significantly increased after educational program (p<0.05). Conclusion: Anxiety of students is in primary school has a high incidence, diagnosis and early treatment could prevent future complications. According to this study findings , communication skills training for mothers is an effective way to reduce the anxiety students. Keywords: Anxiety, student, teacher, School anxiety scale - teacher report (SAS-TR), communication skills training